Influence of Application Design, Customer Service, Privacy Security, and Fulfillment on Customer Loyalty in Language Learning Platforms: The Mediating Role of Customer Satisfaction Among Cakap Users in Jakarta - Hendra Christian; Oliandes Sondakh (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
The rapid growth of digital platforms has transformed the landscape of online education, making customer satisfaction and loyalty critical to the success of subscription-based services. This study investigates the impact of four key service quality dimensions application design, customer service, security, and fulfillment—on customer satisfaction and its mediating effect on customer loyalty, using the Cakap language-learning application as the research context. Data were collected through a structured survey from 255 respondents residing in Jakarta, selected through purposive sampling to ensure relevance. Respondents were required to have completed at least two learning modules on the Cakap platform within the past year, providing a valid and experienced sample for analysis. The findings provide both academic and practical insights. Academically, the study enriches the understanding of customer satisfaction and loyalty dynamics in educational technology platforms, especially in an emerging market context like Indonesia. Practically, it offers actionable recommendations for digital service providers, such as continuously enhancing app design, strengthening security protocols, and optimizing fulfillment processes to meet customer expectations. These strategies are essential for platforms like Cakap to maintain user satisfaction, foster loyalty, and secure sustainable growth in a competitive market.